Cross-cultural Art Curation and Urban Space Revitalization: Insights and Strategies of Hainan Cultural and Creative Week 2024 Forum - Huang, Yuhan (International Journal of Social Sciences and Public Administration, 2024)
In the complex environment of globalization and digitalization in the 21st century, Bourriaud’s "Relational Aesthetics" provides a theoretical basis for us, emphasizing that the value of works of art as a medium of social interaction lies in building relationships between audiences. Taking this as a starting point, the concept of generalized curation transcends the material boundaries of traditional curation. focus on the Lefebvre’s triadic concept of space production, which intergreate realities of landscapes and urban forms, and the conceptual, planned representation through designs. Additionally, it encompasses the symbolic dimensions that influence social identities toghther to illustrate the dynamic nature of spatial existence (Lefebvre, 2012, p81-84). These theoretical frameworks provide a solid theoretical basis for understanding how art curation promotes cross-cultural communication in the context of globalization and how it integrates with urban spatial revitalization. The parallel forum of "Broad Curation and Urban Public Art Power" under the theme of "Resonance · Breaking the waves" of the 2024 Hainan International Cultural and Creative Week, as a dialogue media platform that brings together global wisdom, provides a frontier exploration for the creative transformation of art curation concepts and urban public space. This paper aims to share the perception of the participants and explore the impact of the results of this forum on the field of news communication, especially the urban cultural narrative and public art communication strategy.